2012
DOI: 10.1007/s10928-012-9261-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of red blood cell life-spans in hematologically normal populations

Abstract: Despite the impact of red blood cell (RBC) Life-spans in some disease areas such as diabetes or anemia of chronic kidney disease, there is no consensus on how to quantitatively best describe the process. Several models have been proposed to explain the elimination process of RBCs: random destruction process, homogeneous life-span model, or a series of 4-transit compartment model. The aim of this work was to explore the different models that have been proposed in literature, and modifications to those. The impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Before discussing these issues we describe the two approaches, direct and indirect, commonly used to study RBC survival and the types of RBC samples used in such studies [45]. We then provide a brief literature review.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before discussing these issues we describe the two approaches, direct and indirect, commonly used to study RBC survival and the types of RBC samples used in such studies [45]. We then provide a brief literature review.…”
Section: Introductionmentioning
confidence: 99%
“…Direct models fall primarily into two categories: 1) empirical models for simple curve fitting [9, 13, 32, 42, 44, 46, 53, 65], and 2) “phenomenological” models accounting for macroscopic phenomena such as random destruction of the cells, lifespan-based elimination of the cells, neocytolysis (selective hemolysis of young RBCs under conditions of RBC excess when acutely exposed to increased tissue oxygen content), etc., and method-specific phenomena such as radioactive decay of the label, elution, vesiculation, etc. in the case of labeling by 51 Cr [8, 9, 16, 17, 24, 35, 36, 45, 61]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A comparison of the models (based on both clinical data and direct measures of biotin-labeled RBCs) revealed that an extended version of the transit-compartment model with 12 compartments was superior for description of RBC survival. 7 Although the choice of RBC model was shown to impact predictions of HbA1c in a clinical trial, our results suggest that accurate predictions can still be obtained in a population with type 2 diabetes subjects without inclusion of difference in RBC life-span.…”
Section: Discussionmentioning
confidence: 72%
“…To improve the utilization of data from these shorter trials, where HbA1c has not always reached a stable level, models of glucose and HbA1c homeostasis have been suggested. 5,6,7,8 …”
mentioning
confidence: 99%